2016
DOI: 10.1177/0892705715598357
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations on the failures of woven textile sandwich panels

Abstract: To reveal the deformation, strength, and failure modes of woven textile sandwich composites (WTSCs), test methods suggested by national standards were referenced and discussed to carry out flatwise and edgewise compression experiments, uniaxial stretching experiments, and three-point bending experiments according to the structural characteristics of WTSC. Strength and failure modes of WTSCs in flatwise compression and uniaxial tension were acquired. Anisotropy and size dependency of strength and failure modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Based on the previous research results [17,18,24,25], compressive load–displacement behavior of an IWSC panel has three distinctive stages as shown in Figure 1. These stages are: (1) elastic region, in which the overall behavior of the sandwich panel is linear up to the first maximum load; (2) after the maximum load, the curve declines dramatically as a result of pile buckling and a plateau behavior occurs in which the rate of force at this stage is almost constant; and (3) densification stage where the load increases rapidly as a result of compaction of tilted piles.…”
Section: Problem Definitionmentioning
confidence: 95%
See 1 more Smart Citation
“…Based on the previous research results [17,18,24,25], compressive load–displacement behavior of an IWSC panel has three distinctive stages as shown in Figure 1. These stages are: (1) elastic region, in which the overall behavior of the sandwich panel is linear up to the first maximum load; (2) after the maximum load, the curve declines dramatically as a result of pile buckling and a plateau behavior occurs in which the rate of force at this stage is almost constant; and (3) densification stage where the load increases rapidly as a result of compaction of tilted piles.…”
Section: Problem Definitionmentioning
confidence: 95%
“…Moreover, F k and M k are also the local force and local moment in the kth subelement. Thus, stress components of sub-elements in the local coordinate system are calculated by equations (25)…”
Section: Stress Analysismentioning
confidence: 99%
“…At present, there is no unified test standard for testing the flat compression performance of glass fiber 3D spacer fabric composites in the industry. In this study, GB/T 1453-2005 “Sandwich structure or core flat compression performance test method” was selected based on the material characteristics and experimental equipment [ 17 ]. According to the standard, the test specimens were cut to a size of 60 × 60 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, another study concluded that edgewise compressive and impact properties proposed a significant improvement compared to non-thickened face sheets [21]. Hu et al [22] carried out experimental investigation on the failures of 3DIWF composites. They reported that to attain face-sheet failure mode by long beam flexure, the span must be higher than 36 times of composite's thickness [22].…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al. [22] carried out experimental investigation on the failures of 3DIWF composites. They reported that to attain face-sheet failure mode by long beam flexure, the span must be higher than 36 times of composite's thickness [22].…”
Section: Introductionmentioning
confidence: 99%